PENGARUH DISIPLIN, KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP KINERJA POLISI DI KEPOLISIAN RESOR TOBA SEKTOR BALIGE - Pandy Hasudungan Siahaan; Muhammad Alam Warda Ritonga; Rahmah Dewita; Hendra Paraduan Dongoran; Ari Pranata Surbakti (JRMB (Jurnal Riset Manajemen & Bisnis), 2021)
The problems of this research is how much influence   dicipline to policy performance. How much influence   competency  to policy performance. How much influence   work environment  to policy performance. How much influence   dicipline,   competency,  and work environment to policy performance. The purpose of this research is for know influence and analize of dicipline to policy performance. For know influence and analize of   competency  to policy performance. For know influence and analize of   work environment to policy performance. For know influence  dicipline,   competency,  and work environment to policy performance. The sample in this research is 33 policy, with data analysis technique used is multiple linear regression analysis. The research result     dicipline effect positive and significanly to policy performance.   Competency  effect positive and significanly to policy performance.    Work environment   effect positive and significanly to policy performance. Dicipline,   competency,  and work environment effect positive and significanly to policy performance.